Management of Anesthesia in Preeclamptic Patient with Thrombocytopenia and COVID-19 Infection - Muhamad Ramdani Ibnu Taufik (Journal of Anaesthesia and Pain, 2022)
Background: Coronavirus Disease 2019 (COVID-19) has become a world health emergency. Pregnant women and newborns are two groups of people who are susceptible to disease. Corona virus infection in 2019 has been associated with systemic consequences such as high blood pressure, kidney disease, thrombocytopenia, and liver damage. Anesthetic management of emergency cesarean section in a preeclampsia patient with thrombocytopenia and COVID-19 infection is described in this case report..Case: A 30-year-old woman, G2P1A0 (Gravida: 2, Partus: 1, Abortus: 0), 38 weeks pregnant, came to our hospital complaining of irregular contractions. In addition, the patient had a fever and cough. After 24 hours of testing, a positive test result for COVID-19 was obtained. The patient is then immediately sent to the isolation room. Contractions began regularly within 5 hours, and cervical examination revealed a dilation of 2 cm. Due to the positive impact of COVID-19, the obstetrics and gynecology department chose to undergo a cesarean section. The cesarean section procedure was carried out according to the COVID-19 operating protocol.Conclusion: Patient with severe thrombocytopenia can safely use spinal anesthesia, while COVID-19 patient should avoid general anesthesia to reduce transmission.